Strategic planning of the rolling stock in transportation by rail - Kaminskas, Saulius (Transport, 2002)
Planning the structure and volume of the rolling stock is a key factor of achieving maximum efficiency of transportation by rail as well as forecasting the demand for these it transport facilities. The demand for trains is a time – dependant variable which in each case should be determined by two main approaches. The first method allows us to determine quantitative parameters of rolling stock (i.e. kilometers logged, efficiency, turnover, etc.). The second is based on specially developed mathematical models relying on qualitative characteristics such as relative expenses, efficiency of the particular train, relative expenditure of resources, cost of the trains, etc. Planning the volume of the rolling stock the determination of optimal service life of the trains plays an important role. The calculations involve repair costs, number of overhauls, current expenses and other operational characteristics. First Published Online: 19 Dec 2011